Identification, distribution, and genetic diversity of olive lace bugs and olive flea beetles in the Western Cape province of South Africa - Hlaka, Vaylen (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.